High CO2 favors ionic homeostasis, photoprotection, and lower photorespiration in salt-stressed cashew plants - Souza, Naiara Célida S.; Silveira, Joaquim Albenísio G.; Silva, Evandro Nascimento; Lima Neto, Milton Costa [UNESP]; Lima, Cristina Silva; Aragão, Rafael Magalhães; Ferreira-Silva, Sergio Luiz (Springer Nature, 2019)
The aim of this study was to evaluate the effects of elevated CO2 concentration on acclimation mechanisms related to gas exchange, photochemical activity, photorespiration, and oxidative protection in cashew plants exposed to salinity. Thirty-day-old cashew plants were irrigated with nutrient solution without (control) or with supplemental NaCl (100 mM) for 2 weeks in the greenhouse. Afterward, control and salt-stressed plants were transferred to the growth chamber and supplied with atmospheric (380 µmol mol−1) or high CO2 (760 µmol mol−1) concentrations for 15 days. The results show that elevated CO2 alone reduced the CO2 net assimilation rate (PN) without affecting stomatal conductance (gS) and transpiration rate (E), whereas salinity and NaCl + high CO2 reduced the PN associated with a decrease in gS and E. The potential quantum yield of photosystem II (Fv/Fm) was not altered, but a slight reduction in electron transport rate and photochemical quenching (qP) in response to high CO2 alone or combined with NaCl occurred. However, non-photochemical quenching increased due to the effects of high CO2 and NaCl alone and by their combination. High CO2 alleviated the toxic effects of Na+ favoring the K+/Na+ ratio under salinity. High CO2 coupled with salinity decreased glycolate oxidase activity and the contents of hydrogen peroxide (H2O2), NH4 +, and glyoxylate. Furthermore, we observed increase in membrane damage associated with increased thiobarbituric acid-reactive substances levels under high CO2. High CO2 also decreased ascorbate peroxidase activity, but did not affect superoxide dismutase activity. In general, our data suggest that high CO2 could induce acclimation processes in plants independent of salinity, revealing a set of responses that are more associated with acclimation than with protective responses.
Keywords: Anacardium occidentale; Elevated CO2; Oxidative protection; Photosynthesis; Salinity